2020
DOI: 10.1016/j.cell.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Heterochromatin at the Nuclear Periphery Suppresses Histone Turnover to Promote Epigenetic Inheritance

Abstract: Highlights d Nuclear rim protein Amo1 promotes heterochromatin assembly and stable gene silencing d Amo1 and RNA processing complex RIXC tether heterochromatin to the nuclear periphery d Perinuclear positioning facilitates loading of FACT onto HP1coated heterochromatin d Amo1 and FACT preclude histone turnover to epigenetically propagate heterochromatin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
132
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 85 publications
13
132
1
Order By: Relevance
“…periphery in Amo1 mutants (17), yet we find that silencing is not affected nearly to the same extent by amo1Δ as by boundary deletions, indicating attachment to the nuclear envelope is not how the domain would be constrained. Instead, homologous pairing between the two elements together with TFIIIC binding might define the bottom of the loop (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…periphery in Amo1 mutants (17), yet we find that silencing is not affected nearly to the same extent by amo1Δ as by boundary deletions, indicating attachment to the nuclear envelope is not how the domain would be constrained. Instead, homologous pairing between the two elements together with TFIIIC binding might define the bottom of the loop (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Amo1 and its interacting partner RIXC have been proposed to tether the mating-type region to the nuclear periphery in a subnuclear compartment where reduced histone turnover stabilizes heterochromatin (17). The tethering would rely on the association of RIXC with heterochromatin throughout the silent domain and with the B boxes independent of heterochromatin (17). In both RIXC and Amo1 mutants the mating-type region is displaced from the nuclear periphery and silencing defects are observed (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chromatin region containing the mat locus is localized at the nuclear periphery through the cluster formation of boundary elements on the inverted repeat sequence IR-L/R [89]. A recent report demonstrated that the NE localization of mat locus is mediated through an interaction with nucleoporin Amo1 [31] (see Section 6.2).…”
Section: Proteins Attaching Heterochromatic Regions To the Ne In Meiosismentioning
confidence: 99%